E-COMMERCE & ONLINE MARKETING: RISKS ASSOCIATED WITH ONLINE SHOPPING - Indriyani, Devia (Dinasti Publisher, 2021)
In addition to shopping website, online Business also provides the organization with a lot of advertising opportunities web-based; the strategy to develop the market through online channels has lead to interest, and the seller to apply this strategy to improve their products and services. The use of the innovation (ie PC, Web) in online shopping or marketing to improve marketing operations. The trend of online shopping is becoming faster and faster. Now, the public perception about e-commerce has been adapted and consumers taking risks. In this study, the ideas of different researchers put forward. Researching the trends and status of women in the field of electronic commerce. It is believed that women in this era do very difficult shopping. The risk or the main factor that women prevent their online shopping is a factor of